Corruption as a Heart Disease: An Analysis of Al-Ghazali's Moral and Sufistic Thoughts and Their Relevance for Islamic Education - Dasep Nurjaman (Konsultan Jurnal Ilmiah Indonesia, 2026)
Corruption is a moral problem that is systemic in nature and persists in modern society, including within communities that claim strong religious values. This phenomenon indicates that corruption is not merely caused by weaknesses in legal or institutional systems, but is deeply rooted in moral decay and spiritual illness of the human heart. This article aims to analyze Al-Ghazali’s ethical and Sufi thought in viewing corruption as a disease of the heart, as well as to examine its relevance for contemporary Islamic education. This study employs a qualitative approach using library research methods, drawing primarily on Al-Ghazali’s major works such as Ihya’ ‘Ulum al-Din and Mizan al-‘Amal, along with relevant secondary sources. The findings reveal that Al-Ghazali regards corrupt behavior as a manifestation of inner vices, including excessive love of worldly life (hubb al-dunya), greed, and the inability to control one’s desires. From a Sufi perspective, addressing corruption requires not only external legal sanctions but also an inner process of tazkiyat al-nafs (purification of the soul), the cultivation of virtuous character, and the strengthening of spiritual awareness. This article further discusses the application of Al-Ghazali’s thought within contemporary Islamic education, including schools, pesantren, and higher education institutions, through the integration of moral education, exemplary conduct by educators, and continuous spiritual development. In conclusion, this study affirms that Al-Ghazali’s ethical and Sufi thought remains highly relevant as a foundation for Islamic character education in fostering integrity and moral consciousness, as well as serving as a preventive framework against corruption in the modern era.